IDENTIFYING LEARNING STRATEGIES EMPLOYED BY SUCCESSFUL AND LESS SUCCESSFUL STUDENTS IN READING - Pramudita Mei Setyowati; Sugirin Sugirin (IAIN Syekh Nurjati Cirebon, 2025)
This study aims at identifying successful and less successful students’ learning strategies in reading, and the way they overcome the difficulties in reading. The study uses mixed method in collecting the data. The instruments used are field notes, Oxford’s SILL (Strategy Inventory of Language Learning) questionnaire, interview guide, and document analysis. The study has 2 findings; first, there is no significant difference for both successful and less successful students’ learning strategies with the data of metacognitive, then followed by cognitive, memory, compensation, affective, and social. Second, the students use various platforms, motivation, and way in reading. In addition, this study provides information about successful and less successful students’ learning strategies in reading, so the teacher can assist less successful students in the way the students prefer.